2007
DOI: 10.3141/2038-20
|View full text |Cite
|
Sign up to set email alerts
|

Vehicle Activity Patterns and Emissions in Pune, India

Abstract: India continues to experience substantial economic growth, with increased travel demand for both passengers and goods. As a result, roadway congestion is increasing in many cities and putting significant pressure on India's transportation infrastructure. One key concern is air pollution related to the increased transportation activity. To understand the transportation impacts on air quality, it is necessary to develop and apply appropriate modeling tools to the area of concern. Recently, a new on-road mobile s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…In contrast, in high-income countries such as the USA, the UK, France, Australia, and Japan, national authorities carry out field surveys of drivers for estimating fuel efficiency and annual mileage (Schipper, 2008). In low and middle-income countries, there have been very few attempts to estimate vehicular characteristics (Barth et al, 2007;Huo et al, 2009). These studies reported counts of vehicle types on the road and parking lots, and used only visual inspection.…”
Section: Methods For Estimating Vehicle Use Parametersmentioning
confidence: 99%
“…In contrast, in high-income countries such as the USA, the UK, France, Australia, and Japan, national authorities carry out field surveys of drivers for estimating fuel efficiency and annual mileage (Schipper, 2008). In low and middle-income countries, there have been very few attempts to estimate vehicular characteristics (Barth et al, 2007;Huo et al, 2009). These studies reported counts of vehicle types on the road and parking lots, and used only visual inspection.…”
Section: Methods For Estimating Vehicle Use Parametersmentioning
confidence: 99%
“…The IVE model is specifically 130 designed to calculate emissions from motor vehicles in developing countries for local conditions and has been used extensively in several countries worldwide, including Nepal (Shrestha et al, 2013), India (Barth et al, 2007), China (Guo et al, 2007;Wang et al, 2008), and Iran (Shahbazi et al, 2016). Emissions were estimated by the product of the base emission factors, the correction factors, and the distance travelled or the total starts for each of the vehicle categories.…”
Section: Emissions 221 Emissions From Vehiclesmentioning
confidence: 99%
“…Since we lack survey data for trucks and cars in Kathmandu, we used the data from Pune, India for these two types of vehicles (Barth et al, 2007). The travel distances were obtained from the vehicle registration number and vehicle kilometers traveled (VKT).…”
mentioning
confidence: 99%
“…This is a result of high growth rate of vehicles sold in the city. For another setting in IndiaPune (2011 population-5 million), Barth et al (2007) reported an average age of 4.6 years for passenger cars, for year 2003. The age distribution of vehicular fleet in Indian settings is in complete contrast with those observed in Europe or the United States.…”
Section: Age Profile Of Vehiclesmentioning
confidence: 99%
“…The vehicular characteristics were developed for the city of Pune using video camera recording of traffic, to determine the type of vehicles on road (Barth et al, 2007). The study team also conducted parking lot surveys (visual inspection only) for odometer readings, engine size, and model year and on-board GPS recording to determine vehicle speeds.…”
Section: Introductionmentioning
confidence: 99%